Collaborative information seeking behaviour of student groups in vocational education training institutions in Zanzibar - Nkebukwa, Leontine; Luambano, Ireneus (University of Dar es Salaam Library Journal, 2019)
This stydy investigated collaborative information seeking behaviour of student groups at Vocational Education Training Institutions in Tanzania. Specifically, it sought to find out student group information needs and sources they use to meet their information needs. The study was conducted at Amali Pemba and Amali Zanzibar, and involved observation of two student groups namely tailoring students whose collaborative task was servicing of sewing machine (Amali Pemba) and electronics students whose collaborative task was of repairing a television set (Amali Zanzibar). Data were collected through observations, interviews and Focus Group Discussions. Data collected was qualitatively analysed using thematic analysis techniques. Key findings revealed a wide range of varying student group information needs pursuing two courses, which varied according to tools and type of task assigned to the group. Specifically, the student group servicing sewing machines needed information on sewing machine servicing steps and procedures, and tools to use, and the group responsible for repairing a television set needed information on television faults and how to fix them. Findings further revealed that in order to meet individual group information needs, both students groups relied largely on group members and teachers. Other sources consulted were search engines, internet, and colleagues outside the team or group. The lack of libraries and computers connected to the Internet negatively affected group information seeking and successful accomplishment of group tasks. It was also revealed that respondents were not aware of collaborative search tools which could have enabled users ' to communicate and collaborate synchronously during the information seeking and retrieval. In view of the above, this study recommends that libraries with internet connectivity should be established in all VET institutions, to enable students to access information they need. Furthermore, awareness should be created on collaborative search tools and software and hardware should be acquired to support CIS.